Utilization of Modified Imperata Grass with Cu Nanoparticles as Methylene Blue Adsorbent - Syaikhina Abdul Wakhid; Jauharuddin Luthfi Al Jabbar; Siti Rodiah (Future Science)
Imperata grass microcrystalline cellulose modified with Cu nanoparticles is one of the alternative adsorbents for the reduction of the concentration of methylene blue (MB) dye. The effectiveness of this developed adsorbent in the adsorption process of MB dye was studied. Cu nanoparticles were employed to modify the synthesized cellulose microcrystalline imperata grass. The modified Cu-cellulose adsorbent was successfully produced with brown color and Fourier Transform Infra-Red (FT-IR) identified the presence of OH, CH, and CO peaks. X-ray diffraction (XRD) analysis also confirmed that the produced adsorbent was in microcrystalline phase with a crystal size of 4.402 nm The microcrystalline cellulose-Cu nanoparticles used showed potential as an MB adsorbent, where the MB removal percentage (% A) was 59.574%.